Legionella pneumophila persists within biofilms formed by Klebsiella pneumoniae, Flavobacterium sp., and Pseudomonas fluorescens under dynamic flow conditions. - Catherine R Stewart (Public Library of Science (PLoS), 2012)
Legionella pneumophila, the agent of Legionnaires' disease pneumonia, is transmitted to humans following the inhalation of contaminated water droplets. In aquatic systems, L. pneumophila survives much of time within multi-organismal biofilms. Therefore, we examined the ability of L. pneumophila (clinical isolate 130 b) to persist within biofilms formed by various types of aquatic bacteria, using a bioreactor with flow, steel surfaces, and low-nutrient conditions. L. pneumophila was able to intercalate into and persist within a biofilm formed by Klebsiella pneumoniae, Flavobacterium sp. or Pseudomonas fluorescens. The levels of L. pneumophila within these biofilms were as much as 4 × 10(4) CFU per cm(2) of steel coupon and lasted for at least 12 days. These data document that K. pneumoniae, Flavobacterium sp., and P. fluorescens can promote the presence of L. pneumophila in dynamic biofilms. In contrast to these results, L. pneumophila 130 b did not persist within a biofilm formed by Pseudomonas aeruginosa, confirming that some bacteria are permissive for Legionella colonization whereas others are antagonistic. In addition to colonizing certain mono-species biofilms, L. pneumophila 130 b persisted within a two-species biofilm formed by K. pneumoniae and Flavobacterium sp. Interestingly, the legionellae were also able to colonize a two-species biofilm formed by K. pneumoniae and P. aeruginosa, demonstrating that a species that is permissive for L. pneumophila can override the inhibitory effect(s) of a non-permissive species.